1999
DOI: 10.1159/000029427
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol and Salmeterol in Partially Reversible Chronic Obstructive Pulmonary Disease: A Crossover, Placebo-Controlled Comparison of Onset and Duration of Action

Abstract: Background: In contrast to the well-known activity profile in asthma, the precise efficacy and optimum dose schedules of long-acting β2-agonists in chronic obstructive pulmonary disease (COPD) are not clear. Objective: In this study, we aimed to compare the onset and the duration of action of a single inhalation of formoterol and salmeterol in COPD patients having partially reversible airway obstruction. Methods: In a double-blind, randomized, crossover and placebo-controlled study design, the respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 13 publications
3
39
1
1
Order By: Relevance
“…In contrast, salbutamol and formoterol elicited a significant increase of IC 5 min after administration, while salmeterol and oxitropium showed a significant IC increase only after 15 and 30 min, respectively. In terms of FEV1, a faster onset of action has been reported for salbutamol and formoterol than salmeterol and oxitropium in COPD patients [30]. In line with previous results [17], these data show that there is a dichotomy in the time course of changes in FEV1 and IC after bronchodilator administration.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, salbutamol and formoterol elicited a significant increase of IC 5 min after administration, while salmeterol and oxitropium showed a significant IC increase only after 15 and 30 min, respectively. In terms of FEV1, a faster onset of action has been reported for salbutamol and formoterol than salmeterol and oxitropium in COPD patients [30]. In line with previous results [17], these data show that there is a dichotomy in the time course of changes in FEV1 and IC after bronchodilator administration.…”
Section: Discussionsupporting
confidence: 90%
“…(23,24) In a study involving 20 patients with partially reversible COPD and similar to the present study in design (formoterol and a placebo were compared), a significant response was observed even within 10 or 20 min after formoterol administration. (25) In our study, patients with stable COPD presented a substantial improvement in FEV 1 at 30 min after formoterol administration, indicating that formoterol has an immediate bronchodilator effect. Other studies have indicated that formoterol administraIn a study involving 133 patients with asthma and 116 with COPD, (20) the mean increase in FEV 1 was 307 and 120 mL , respectively, indicating that an increase in FEV 1 of 200 mL is a good cut-off point to differentiate one disease from the other.…”
Section: Discussionsupporting
confidence: 56%
“…The AE profile was similar in each group, although proportionally more patients reported COPD events in the placebo group than in the active treatment groups (17,13,19 and 26% in the budesonide/formoterol, budesonide, formoterol and placebo groups, respectively). No treatment-related patterns were discernable regarding the incidence or cause of death (table 2).…”
Section: Safetymentioning
confidence: 87%
“…Studies have also shown that formoterol and salmeterol can improve exercise tolerance [9,10] and HRQL [11,12] in patients with COPD compared with other treatments. The unique rapid-and long-acting properties of formoterol, however, give this treatment a faster onset of effect [13], similar to salbutamol [14].Treatment with inhaled corticosteroids has shown clinical benefits in COPD by improving exacerbations, symptoms, lung function and HRQL [15][16][17][18]. SIN and TU [19] observed that elderly patients recently…”
mentioning
confidence: 99%
See 1 more Smart Citation